MATHEMATICAL MODEL OF THE UNIVERSITY’S DIGITAL PROFILE AS A PREDICTOR OF DEMAND FOR EDUCATIONAL SERVICES - Vasyliv, Volodymyr; Hrytsiuk, Petro; Beztelesna, Liudmyla; Joshi, Olena (Current Problems of Sustainable Development, 2026)
In the modern era of total digital transformation sweeping through global and national higher education systems, a university’s online visibility and digital performance have emerged as critical parameters influencing competitive institutional advantages and student recruitment success. This paper addresses the urgent academic and practical problem of quantifying how the multi-layered digital profiles of Ukrainian higher education institutions directly affect their enrollment outcomes, specifically measured by the total volume of admission applications submitted by prospective students. The primary objective of this investigation is to construct, evaluate, and empirically validate a robust mathematical model that precisely describes and predicts these complex interdependencies. To achieve this objective, the research employs a quantitative methodological framework, using multiple linear regression on an extensive dataset compiled from 173 prominent Ukrainian universities featured in the authoritative «TOP−200 Ukraine» academic ranking. The analytical model incorporates a comprehensive array of independent variables, including key website performance metrics such as traffic volume, domain authority, backlink profiles, and user behavioral factors. Additionally, institutional positions in global and domestic rankings, such as Webometrics, alongside crucial control parameters including institutional type, size, geographical region, the scientific reputation measured via the Hirsch index, and the regional pool of applicants based on National Multi-Subject Test (NMT) statistics, were systematically analyzed. The empirical findings demonstrate that the optimized regression model has high explanatory power, accounting for approximately 72,1% of the total variance in student admission application volume. The statistical analysis reveals that the volume of organic search traffic and the total number of unique referring domains linking to a university’s web platform exert a highly significant positive impact on attracting potential applicants. Furthermore, the empirical evidence confirms the substantial influence of institutional size, established scientific reputation, and regional demographic potential. Consequently, these insights underscore the strategic necessity for higher education administrators to actively invest in search engine optimization (SEO), comprehensive website development, and high-quality link-building practices. In practice, this study provides a valuable, evidence-based decision-making framework for university marketing departments, offering specific empirical foundations to optimize the digital footprints and recruitment strategies of Ukrainian higher education institutions.